Rancang Bangun Alat Penyemprot Herbisida (Knapsack Sprayer) Elektrik Berbasis Panel Surya 20 Wp Paralel - Gali Triyani; Fardhan Arkan; M Yonggi Puriza; Welly Yandi; Yandi Anzari; Habib Satria; Hanalde Andre (Department of Electrical Engineering, UNJANI, 2022)
A classic problem that hinders farmers from spraying herbicide liquids because they still use a herbicide liquid sprayer system in amanual way. This research aims to produce electric herbicide sprayers that are efficient and effective for the community, as well as to engenalize and utilize renewable energy as energy that is easy to obtain and environmentally friendly, especially in agriculture. The sources produced by the 20Wp solar panels are in the form of Voltage, Current, Power and Electrical Energy. Solar panel measurements are taken for 7 days, starting from 08.00 WIB to 15.00 WIB. The results obtained for the largest average values of Voltage, Amperes, and Power were on day 7 where the Voltage was 13.72V, Current was 0.43A, and Power was 5.88W. S. Sexplained for the average value of the largest Electrical Energy was on day 2 and day 5 of 0.60Wh. The effect in taking solar panel data in this study was Light Intensity, with the largest average n ilai being on the 7th day, which was 905.8 W/m2. The manufacture of electric herbicide sprayers based on 20 Wp solar panels has been carried out with very effective results and functions in accordance with the purpose of making tools, namely introducing renewable energy as alternative energy that is easily available, especially in agriculture